Complex Interaction of Hb Q-Thailand (HBA1: c.223G>C) with β-Thalassemia/Hb E (HBB: c.79G>A) Disease - Sitthichai Panyasai (2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group. Hb Q-Thailand [α74(EF3)Asp→His (α1), GAC>CAC, HBA1: c.223G>C] is an abnormal hemoglobin (Hb) frequently found in Thailand and Southeast Asian countries. The association of the αQ-Thailandallele with other globin gene disorders has important implications in diagnosis. Here, we report how to diagnose the coinheritance of Hb Q-Thailand with β-thalassemia (β-thal)/Hb E disease in four Thai samples from high performance liquid chromatography (HPLC) and capillary electrophoresis (CE) testing results. Understanding of the HPLC chromatogram and CE electropherogram patterns of this complex mutation is important for interpretation of testing results and providing genetic counseling.